Determinants of Indonesia Import in 1981-2014 - Imam, Muhammad Kholisul; Santosa, Dwi Budi (Universitas Negeri Semarang, 2017)
Import becomes one of the components to calculate economic growth. During 1981-2014, a series of variation in Indonesia import has occured. In addition, the increase of GDP, the occurrence of domestic economic shocks, the increase of inflation rate, the increase of population and the increase of total reserves were alleged to influence the variation of Indonesia import. This research aims to analyze the factors affecting Indonesia imports. The variables used in this research are GDP growth, domestic economic shocks, inflation rate, population, and total reserves. Econometric analysis model used in this research is Error Correction Model (ECM). The results of this research reveal several outcomes: (1) the data is stationary at first difference; (2) the data is cointegrated meaning that there is a connection in long-term parameters; and (3) ECT coefficient/speed of adjustment is -0.6881 and significant is at ? = 5% meaning that the model used is valid. The conclusions of this research are: (1) In the short term, domestic economic shocks, inflation rate, population, and total reserves have a significant effect on the Indonesia import; (2) In the long term, inflation rate, population, and total reserves have a significant effect on Indonesia import.